2021
DOI: 10.21037/jtd-21-913
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of DNA microarray for detecting rifampicin and isoniazid resistance in Mycobacterium tuberculosis

Abstract: Background: While rifampicin (RFP) and isoniazid (INH) are the most commonly used first-line antituberculosis drugs, multidrug resistance in Mycobacterium tuberculosis poses a threat to the success of tuberculosis (TB) control programs. Clinical practice guidelines and expert consensuses recommend drug susceptibility testing (DST) before the initiation of antituberculosis treatment. However, traditional DST is time-consuming and has high requirements for laboratory conditions. The recently developed molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In those conditions, it is recommended to repeat the Xpert testing in case of a first positive result. Other in-house molecular methods are also available, and they might be useful especially at the local level or in low-resource settings since they are relatively inexpensive, see for example [52,53]. However, standardization and cross-laboratory reproducibility are difficult to obtain with these methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those conditions, it is recommended to repeat the Xpert testing in case of a first positive result. Other in-house molecular methods are also available, and they might be useful especially at the local level or in low-resource settings since they are relatively inexpensive, see for example [52,53]. However, standardization and cross-laboratory reproducibility are difficult to obtain with these methods.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the MGIT, the assay reported a sensitivity and a specificity of 84.0% and 94.0% for RIF-resistance detection and 73.0% and 97.0% for INH-resistance detection. However, it was not possible to determine which mutations in the rpoB, inhA and katG genes were targeted by the microarray system, making it difficult to compare it with other DST methods [52].…”
Section: Other Molecular Methodsmentioning
confidence: 99%
“…Although microarray can detect many genes at the same time, for simplicity of procedure it can be used in identifying mutations in the rpoB , gyrA, and pncA genes, predicting resistance to RIF, fluoroquinolones, and PZA, respectively (Havlicek et al 2019 ; Wade et al 2004 ). For this purpose, samples should be placed into a microarray platform and recorded the results with a microarray scanner such as LuxScan™ from CapitalBio Co. (Sun and Sun 2021 ).…”
Section: Assays and Methodsmentioning
confidence: 99%
“…Ma et al (82) developed and evaluated a solid-phase chip for the simultaneous detection of 15 types of bacteria directly from respiratory tract specimens of patients with pneumonia, thus reducing detection time, facilitating the early administration of antimicrobial drugs and preventing bacterial resistance caused by empirical antibiotic treatment. Recent studies have shown that the CapitalBio DNA chip (CapitalBio Corporation) can detect the resistance of MTB to rifampicin and isoniazid, and the corresponding gene mutations within 6 h, which is quicker and more accurate than traditional bacterial culture and drug susceptibility tests (83)(84)(85). Currently, a number of automatic detection platforms based on solid-phase chips are entering the market.…”
Section: Gene Chip Technologymentioning
confidence: 99%